A novel caspase-associated recruitment domain (CARD) containing protein (CgCARDCP-1) involved in LPS recognition and NF-κB activation in oyster (Crassostrea gigas). Issue 79 (August 2018) - Wang, Feifei; Yu, Zichao; Wang, Weilin; Li, Yiqun; Lu, Guangxia; Qu, Chen; Wang, Hui; Lu, Mengmeng; Wang, Lingling; Song, Linsheng
Abstract: Caspase-associated recruitment domain (CARD) containing proteins play critical roles in molecular interaction and regulation of various signaling pathways, such as the activation of caspase and NF-κB singling pathway in the process of apoptosis or inflammation. In the present study, a novel CARD containing protein (designed Cg CARDCP-1) was identified and characterized from oyster Crassostrea gigas . Molecular feature analysis revealed that, the open reading frame (ORF) of Cg CARDCP-1 gene was 759 bp encoding a polypeptide of 253 amino acids with a conserved N-terminal CARD domain and two transcriptional coactivator p15 (PC4) domains in C-terminus. Homologous alignment showed that the amino acid sequence of Cg CARDCP-1 shared 30%–46% identity with that of caspase-2. By RT-PCR detection, the mRNA transcripts of Cg CARDCP-1 were found to be widely distributed in various tissues of oyster with the highest expression level in hemocytes and mantle. And Cg CARDCP-1 protein was mostly distributed in the cytoplasm of oyster hemocytes as shown by immunohistochemistry. Moreover, the Cg CARDCP-1 mRNA expression level in hemocytes was significantly up-regulated after lipopolysaccharide (LPS) and Vibrio splendidus stimulations. The recombinant Cg CARDCP-1 displayed strong binding activity with LPS in vitro . In addition, after transfected into the HEK-293T cell with luciferase reporter system, Cg CARDCP-1 could significantly promote the NF-κB activation (1.29-fold, p  < 0.05) compared to that in the control group. These results collectively demonstrated that the Cg CARDCP-1 might serve as a recognition molecule for LPS and a regulator of NF-κB activation in the immune response of oyster. Highlights: A novel caspase recruitment domain (CARD) containing protein ( Cg CARDCP-1) was identified from Crassostrea gigas. The expression level of Cg CARDCP-1 mRNA in haemocytes was up-regulated after LPS and Vibrio splendidus stimulations. The recombinant Cg CARDCP-1 exhibited significant binding activities towards LPS. Cg CARDCP-1 might be involved in the activation of NF-κB signaling pathway.